Factors influencing the initiation, performance and precision of the hit in fencing - Stein, J. F. (1st International Congress on Science and Technology in Fencing, Barcelona, 15-17 February 2008, 2008)
This presentation puts a series of studies into perspective which were undertaken with and for elite French fencers regarding the analysis of factors which may influence motor performance as far the initiation and the execution and accuracy of the touch. In terms of a bio-informational approach, the relationships between reaction time (RT), movement time (MT) and accuracy (% targets hit) provides an account of the processes of programming and movement control and the strategies implemented. The influence of factors on these strategies such as the type of uncertainty the athlete is afflicted with, the specialisation that is connected to the weapon, fatigue after exercise or the athlete`s lateralization can be analysed throughout the sports season.